Persepsi Jurai Tue Terhadap Nilai Filosofi Arca Imam Peninggalan Zaman Batu (Megalitikum) Di Kabupaten Lahat: Studi Di Desa Simpur Kabupaten Lahat - Okta Riadi; Desy Misnawati; Fathur Rahman (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
This study aims to determine the perception of Jurai tue in Simpur village in understanding and applying the philosophical value of the priest statue, one of the historical relics of the megalithic era, in carrying out daily activities. This statue symbolizes the figure of a leader, and is described as a strong figure with a slightly protruding head. Round eyes, wide mouth and flat nose. There are bracelets on the legs and arms, and the second is a human figure who is usually called a priest statue by the surrounding community. His eyes are round, his nose is flat, and his mouth is wide. On the head of this statue has a protrusion that looks like a headdress. In this study, the researcher used descriptive qualitative research methods. and also in this study using phenomenological theory with data collection techniques in the form of interviews, literature studies and also documentation. The results of this study aim to determine the jurai tue's perception of the philosophical value of the priest statue in Simpur village, Lahat district.